The First Year Inventory: a longitudinal follow-up of 12-month-old to 3-year-old children. (September 2013) - Turner-Brown, Lauren M; Baranek, Grace T; Reznick, J Steven; Watson, Linda R; Crais, Elizabeth R
The First Year Inventory is a parent-report measure designed to identify 12-month-old infants at risk for autism spectrum disorder. First Year Inventory taps behaviors that indicate risk in the developmental domains of sensory–regulatory and social–communication functioning. This longitudinal study is a follow-up of 699 children at 3 years of age from a community sample whose parents completed the First Year Inventory when their children were 12 months old. Parents of all 699 children completed the Social Responsiveness Scale–Preschool version and the Developmental Concerns Questionnaire to determine age 3 developmental outcomes. In addition, children deemed at risk for autism spectrum disorder based on liberal cut points on the First Year Inventory, Social Responsiveness Scale–Preschool, and/or Developmental Concerns Questionnaire were invited for in-person diagnostic evaluations. We found 9 children who had a confirmed diagnosis of autism spectrum disorder from the sample of 699. Receiver operating characteristic analyses determined that a two-domain cutoff score yielded optimal classification of children: 31% of those meeting algorithm cutoffs had autism spectrum disorder and 85% had a developmental disability or concern by age 3. These results suggest that the First Year Inventory is a promising tool for identifying 12-month-old infants who are at risk for an eventual diagnosis of autism spectrum disorder.